Montesquieujeva podoba sodnika v luči doktrine delitve oblasti - Spruk, Jure (Pravnik, 2024)
The author discusses Montesquieu’s image of the judge, an iconic figure in legal theory and legal philosophy, in light of his doctrine of the separation of powers as presented in The Spirit of the Laws. Montesquieu’s discussion appears somewhat incoherent: he sees law as an important social apparatus, yet simultaneously rejects a stable judicial institution to adapt the legal system to a given social reality. He even defines the separation of judicial power from executive power as a criterion for determining moderate regimes, yet perceives judicial power as void. This incoherence arises from the epistemology of natural law, which rejects creativity in favour of discovery of laws. Montesquieu’s image of the judge fits perfectly with the 19th century ideology of codification, which idealises the completeness and clarity of a code of laws. Montesquieu’s rigidly constructed doctrine of separation of powers can justify his anaemic judge only outside the real circumstances of judicial decision-making, for law is created by a judge, not discovered.